1995
DOI: 10.1002/pro.5560040212
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of the interface between adjacent catalytic chains promotes domain closure in escherichia coli aspartate transcarbamoylase

Abstract: Aspartate transcarbamoylase from Escherichia coli is a dodecameric enzyme consisting of two trimeric catalytic subunits and three dimeric regulatory subunits. Asp-100, from one catalytic chain, is involved in stabilizing the C1-C2 interface by means of its interaction with Arg-65 from an adjacent catalytic chain. Replacement of Asp-100 by Ala has been shown previously to result in increases in the maximal specific activity, homotropic cooperativity, and the affinity for aspartate (Baker DP, Kantrowitz ER, 1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In the R‐state, Glu50 forms interdomain bridging interactions with Arg167 and Arg234, of the ASP domain, stabilizing the R‐state. Mutation of Glu50 to Ala results in a R‐state destabilized mutant with a 19‐fold reduction in activity compared to wild‐type 29. SAXS studies showed that upon addition of CP and succinate (an aspartate analog) the E50A mutant is in the T state in contrast to the wild‐type enzyme, which exists in the R state 29, 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the R‐state, Glu50 forms interdomain bridging interactions with Arg167 and Arg234, of the ASP domain, stabilizing the R‐state. Mutation of Glu50 to Ala results in a R‐state destabilized mutant with a 19‐fold reduction in activity compared to wild‐type 29. SAXS studies showed that upon addition of CP and succinate (an aspartate analog) the E50A mutant is in the T state in contrast to the wild‐type enzyme, which exists in the R state 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Glu50 to Ala results in a R‐state destabilized mutant with a 19‐fold reduction in activity compared to wild‐type 29. SAXS studies showed that upon addition of CP and succinate (an aspartate analog) the E50A mutant is in the T state in contrast to the wild‐type enzyme, which exists in the R state 29, 30. However, the E50A enzyme–PALA complex exists in the R structure similar to the structure of the wild‐type enzyme in the presence of PALA or substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The three very important interactions between E. coli ATCase monomers in the catalytic trimer have been identified to be Lys-41, Asp-100, and Asp-90 of one monomer that form salt links with Glu-37, Arg-65, and Arg-269 of the adjacent subunit [36,37]. Multiple sequence alignment of P. aeruginosa ATCase with other trimeric ATCases (S1 Fig) showed that two of the three interactions are partially conserved in P. aeruginosa.…”
Section: Plos Onementioning
confidence: 99%